2020
DOI: 10.3390/su12198033
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Capital Lens for a Sustainable Bioeconomy: Determining the Unrealised and Unrecognised Services from Nature

Abstract: Human activity has led to degradation of the natural environment, with far-reaching impacts for society and the economy, sparking new conceptual framings for how people interact with, and depend upon, the environment. The bioeconomy and natural capital concepts both blend economics and natural sciences and propose new interdisciplinary, environmental sustainability framings. Despite this similarity, the two concepts are rarely applied together. This paper applies a natural capital lens to the bioeconomy at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Indeed, increasing regulatory and market forces may encourage landowners and managers to share knowledge on the impact of land use decisions on natural assets (Guerry et al, 2015; Solar Energy UK, 2019). This could open further channels of long‐term collaboration between interdisciplinary researchers, practitioners and asset managers to aim towards a full systems approach (Neill et al, 2020) to integrate energy–environment–society research to better understand and communicate NC‐ES sustainability within SPs. Land managers would focus on delivering locally targeted environmental outcomes, while researchers would benefit from data availability to provide research‐, industry‐ and policy‐oriented output to convey an integrated picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, increasing regulatory and market forces may encourage landowners and managers to share knowledge on the impact of land use decisions on natural assets (Guerry et al, 2015; Solar Energy UK, 2019). This could open further channels of long‐term collaboration between interdisciplinary researchers, practitioners and asset managers to aim towards a full systems approach (Neill et al, 2020) to integrate energy–environment–society research to better understand and communicate NC‐ES sustainability within SPs. Land managers would focus on delivering locally targeted environmental outcomes, while researchers would benefit from data availability to provide research‐, industry‐ and policy‐oriented output to convey an integrated picture.…”
Section: Discussionmentioning
confidence: 99%
“…to share knowledge on the impact of land use decisions on natural assets (Guerry et al, 2015;Solar Energy UK, 2019). This could open further channels of long-term collaboration between interdisciplinary researchers, practitioners and asset managers to aim towards a full systems approach (Neill et al, 2020)…”
Section: Discussionmentioning
confidence: 99%
“…The loss of biodiversity, changes in land use and spatial planning, climate change, the rise of circular and bioeconomies, and the development of new public policies and strategies have all contributed to the rise of ESs as a major topic on the public agenda in recent years (Neill et al, 2020;Verkerk et al, 2020;Raihan and Tuspekova, 2022b). The development of a tool for measuring TEV is necessary to support political decision-making and to inform citizens and businesses about the benefits and costs inherent in projects, programs, and policies .…”
Section: The Necessity Of Evaluating Ecosystem Servicesmentioning
confidence: 99%
“…Despite the diversity of the publications and the novelty of the methods employed, a review of 45 documents and articles conducted in 2020 revealed that eight topics predominated: (a) the technical and economic feasibility of biomass extraction and use; (b) frames and tools; (d) the sustainability of biology-based processes, products, and services; (e) the ecological sustainability of a bioeconomy; and (f) the governance of a bioeconomy. Despite the fact that bioeconomy and NC both present new interdisciplinary frameworks for environmental sustainability by combining economics and the natural sciences, they are rarely used in tandem (Neill et al, 2020;Raihan, 2023k). With a circular economy in place, technological and productive tasks won't drain ecological systems to the point of exhaustion (Raihan and Tuspekova, 2023a).…”
Section: Ecosystem Services and Challengesmentioning
confidence: 99%
“…The development of a circular bioeconomy underpinned by sustainable renewable biological resources from primary production and its associated technological, product, and systemic solutions has been proposed as offering a solution to support a reduction in emissions within the broader agricultural and livestock sectors, while at the same time offering new business and innovation opportunities in traditional primary sectors [8]. Solutions vary from synthetic and seaweed-based additives, which can potentially inhibit rumen methane emissions [9,10], to the displacement of fossil-based materials and fuels with new bio-based materials and biofuels produced from agricultural by-products [11][12][13], to nature-based solutions [14,15]. Many synergies for bioeconomy development exist within primary sectors, and some of these are explored in Figure 1.…”
Section: Introductionmentioning
confidence: 99%